Primary Budd-Chiari syndrome versus sinusoidal obstruction syndrome: a review - Lu, Feifei; Jia, Siqi; Lu, Huiyuan; Zhao, Haonan; Li, Zhe; Zhuge, Yuzheng; Romeiro, Fernando Gomes [UNESP]; Mendez-Sanchez, Nahum; Qi, Xingshun (Taylor & Francis, 2024)
Budd-Chiari syndrome (BCS) and sinusoidal obstruction syndrome (SOS) are two major vascular disorders of the liver, of which both can cause portal hypertension related complications, but their locations of obstruction are different. BCS refers to the obstruction from the hepatic vein to the junction between the inferior vena cava and right atrium, which is the major etiology of post-sinusoidal portal hypertension; by comparison, SOS is characterized as the obstruction at the level of hepatic sinusoids and terminal venulae, which is a cause of sinusoidal portal hypertension. Both of them can cause hepatic congestion with life-threatening complications, especially acute liver failure and chronic portal hypertension, and share some similar features in terms of imaging and clinical presentations, but they have heterogeneous risk factors, management strategy, and prognosis. Herein, this paper reviews the current evidence and then summarizes the difference between primary BCS and SOS in terms of risk factors, clinical features, diagnosis, and treatment.
Keywords: Budd-Chiari syndrome; hepatic vein; inferior vena cava; obstruction; outcome; risk factor; sinusoidal obstruction syndrome; treatment